1992
DOI: 10.1021/jm00083a009
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor agents. 123. Synthesis and human DNA topoisomerase II inhibitory activity of 2'-chloro derivatives of etoposide and 4.beta.-(arylamino)-4'-O-demethylpodophyllotoxins

Abstract: The 2'-chloro derivatives of etoposide and 4 beta-(arylamino)-4'-O-demethylpodophyllotoxins have been synthesized and evaluated for their inhibitory activity against the human DNA topoisomerase II as well as for their activity in causing cellular protein-linked DNA breakage. The results showed that none of the compounds are active as a result of the C-2' chloro substitution on ring E. This would suggest that the free rotation of ring E is essential for the aforementioned enzyme inhibitory activity. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The increased activity of 4-alkylamino derivatives on human topo II inhibition and cellular protein linked DNA breakage [83], led to the synthesis and testing of a large number of C(4)-Nsubstituted analogues. 4β-Anilino-, 4β-amido-, 4β-arylamino-and 4β-alkyamino-derivatives were prepared [62,74,83,[84][85][86]. The bulky substitution at the C(4) position usually enhances the cytotoxicity and topo II inhibition activity [87,88].…”
Section: Ring C Modificationsmentioning
confidence: 99%
“…The increased activity of 4-alkylamino derivatives on human topo II inhibition and cellular protein linked DNA breakage [83], led to the synthesis and testing of a large number of C(4)-Nsubstituted analogues. 4β-Anilino-, 4β-amido-, 4β-arylamino-and 4β-alkyamino-derivatives were prepared [62,74,83,[84][85][86]. The bulky substitution at the C(4) position usually enhances the cytotoxicity and topo II inhibition activity [87,88].…”
Section: Ring C Modificationsmentioning
confidence: 99%
“…16 Additionally, Hu et al found that once a 36 chlorine atom was introduced at the C-2' position of podophyllotoxin derivatives, the 37 corresponding compounds showed no significant cytotoxicity. 17 More recently, we have 38 prepared a series of oxime sulfonate derivatives of picropodophyllotoxin 18 (2, Figure 1) and 39 4α/β-acyloxy-2′(2′,6′)-(di)halogenopodophyllotoxin derivatives 19,20 (3, Figure 1) as 40 insecticidal agents, and found some derivatives exhibited more potent insecticidal activity 41 than toosendanin, a commercial botanical insecticide isolated from Melia azedarach. Where T is the mortality rate in the tested compounds group, and C is the mortality rate in the 210 blank control group (T and C were expressed as percentages).…”
Section: Introduction 23mentioning
confidence: 99%
“…A total of 143 epipodophyllotoxin analogues (Tables 1 and 2 ) were used in the study, which were collected from different published articles [16][17][18][19][20][21][22][23][24][25][26][27]. These compounds were tested for their ability to form intracellular covalent topoisomerase II-DNA complexes.…”
Section: Preparation Of the Ligandsmentioning
confidence: 99%
“…Efforts for improving their clinical efficacy further by overcoming the drug resistance, myelosuppresion and poor bioavailability problems [15] associated with them, were continued to be challenging. Over the years a number of laboratories throughout the world engaged in the synthesis and testing of epipodophyllotoxin derivatives [16][17][18][19][20][21][22][23][24][25][26][27] to prepare new more potent and less toxic analogues, that is, with better therapeutic indices. The mechanism of action of any drug is very important in drug development.…”
Section: Introductionmentioning
confidence: 99%